Modelling and Simulation of Mechanical Loads and Residual Stresses in Deep Rolling at Elevated Temperature - Sven Kuschel; Tobias Kinner-Becker; Robert Zmich; Jens Sölter; Daniel Meyer (Journal of Manufacturing and Materials Processing, 2021)
Based on the concept of Process Signatures, the deep rolling process is analyzed, aiming at functional relationships between material modifications and internal material loads during the process. The focus of this work is to investigate the influence of the workpiece temperature on the generated residual stress components. For this purpose, extensive finite element simulations of deep rolling were conducted, taking into account the effect of neighboring tool paths on the internal material loads and residual stress. A kinematic strain hardening model was parameterized and utilized and the simulations were validated experimentally. Simulated residual stresses agree qualitatively well with measurements and show a strong influence of the workpiece temperature as expected. Process Signature Components were generated, taking into account the maximal and minimal residual stress as well as their respective positions beneath the workpiece surface.